Pelatihan Menulis Korespondensi Bisnis Bagi Mitra Kadin Ponorogo - Sugianto, Alip; Sugianto, La Ode; Priatna, Yolan; Purwaningrum, Titis (Journal of Community Services in Sustainability, 2024)
Kadin Ponorogo as the parent organization for entrepreneurs has a role in providing education and training services for Kadin partners. There are some institutions or companies, especially MSMEs in Ponorogo, who do not understand the strategy of writing good correspondence. Therefore, as an effort to overcome this problem, the Ponorogo Chamber of Commerce and Industry in collaboration with the Muhammadiyah University of Ponorogo held correspondence writing training. The methods used are theory and practice. Theory is an effort to provide valuable understanding of the concept of good correspondence, and is strengthened by practice to find out the extent of understanding of correspondence. As a result, the correspondent learned about good writing strategies by applying strategies such as ATM (Observe Modified Imitation) and the correspondent succeeded in creating examples of good correspondence.